Clonal Identification of Poplars by Isozvme Analysis - Thakur, Sanjeev; Wuelisch, G. Von (Indian Forester, 2001)
Horizontal starch electrophoresis was used to distinguish different Poplar (Populus deltoides) clones. The enzymes; Malate dehydrogenase, Phosphoglucose isomerase, Isocitrate dehydrogenase and 6 phospho-gluconate-dehydrogenase were polymorphic. On the basis of isozyme analysis, the clones could be grouped into 5 groups. Three out of nine clones were identified by isozyme patterns.